ANALISIS KUALITAS PELAYANAN, PENGARUHNYA TERHADAP IMAGE - Hanif Mauludin (Akutansi Bisnis & Manajemen ( ABM ), 2000)
The study was undertaken with the rationale that service quality is an important aspect for organization leaders to consider, especially for service oriented organizations to satisfy their customer. Satisfying the customers provides the organization with a good corporate image. A good corporate image serves as an effective strategy in winning the competition with other businesses of the same type. Leading companies who wish to keep their status should always keep service quality mind. It has to be an absolute concern as the organization does not only have to face the competitors but also the customers who continuously change, vary, and are aware of their needs. Therefore, continuous enhancement of service quality has to be provided. This study is aimed at 1) determining the service quality level of public hospital in Tuban, form the patient perspective; 2) determining influence of service quality on corporate image. Service quality is measured in five dimensions know as servqual technique. The five dimensions serve as tangibility (x1), reliability (x2), responsiveness (x3), assurance (x4), empathy (x5). The research was conducted at the regional public hospital of Tuban, with the VIP, first class, and second class patients as the analysis units. Sampling was done by stratified random sampling technique obtain 73 respondents. Gap analysis was used by comparing performance and expectation, while regression analysis was used by the inter-variable relationship of the hypothesis. As many as 18 items were used as main instrument of the questionnaire which was distinguished into five quality variables used to collect the data, both through interview and questionnaires to be filled out by respondents. Verification of research instruments showed high reliability and validity. The result of this study showed that gap analysis technique used could provide information from the patient?s perspective at the service quality at the public hospital of Tuban was good. Statistical testing revealed that significant influence was evident of service quality and corporate image, with R=0.83 and R2=0.66. The most dominant variables, however, for corporate image were tangibility and reliability. In conclusion, the result of this study support some theories developed by the Parasuraman (Servqual), Brown (Customer Satisfaction/Revenue Enhancement Models) and Elhaitammy (Service Excellence). Furthermore, this confirms the hypothesis that significant influence is evident quality on the corporate image